2022
DOI: 10.3389/fenvs.2022.991022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impact of digital economy on urban environmental pollution: Empirical evidence from 277 prefecture-level cities in China

Abstract: With the recent technological advancements, such as the internet, big data, and cloud computing, China’s digital economy plays a significant role in economic development. However, the digital economy may also affect the environmental quality, but the prevailing literature is scant on how the digital economy affects urban environmental pollution. To fill this gap, this study established an urban digital economy index system based on 277 prefecture-level cities in China and calculated their digital economy indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Contrarily, another investigation highlighted that the growth of the digital economy resulted in a significant decrease in pollution levels in the eastern region and a notable reduction in CO 2 emissions in the western region [49]. Bai et al (2022) [50] corroborated these findings, revealing that larger cities, with their advanced digital infrastructure and systems, were more effective in reducing pollution. Nevertheless, the influence of the digital economy and big data is not universally positive.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Contrarily, another investigation highlighted that the growth of the digital economy resulted in a significant decrease in pollution levels in the eastern region and a notable reduction in CO 2 emissions in the western region [49]. Bai et al (2022) [50] corroborated these findings, revealing that larger cities, with their advanced digital infrastructure and systems, were more effective in reducing pollution. Nevertheless, the influence of the digital economy and big data is not universally positive.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Additionally, it has the potential to decrease environmental pollution in nearby regions by breaking down spatial and information barriers (Xu et al, 2022;Yi et al, 2022). The impact of DE on environmental pollution exhibits regional heterogeneity, with a less inhibitory effect observed in non-resource-based cities, western cities, and small cities (Bai et al, 2022;Che and Wang, 2022;Huang et al, 2023). However, the exponential growth of DE has resulted in a substantial rise in energy usage associated with digital infrastructure and the overall ICT industry.…”
Section: De and Environmental Pollutionmentioning
confidence: 99%
“…In terms of environmental protection, there is a non-linear relationship between the digital economy and carbon emissions. Some studies have shown that the digital economy has slowed down carbon emissions, reduced air pollution, and promoted green development of the economy [ 8 10 , 25 , 26 ], But there are also studies indicating that the digital economy will increase energy consumption [ 27 ]. At the micro level, digital technologies have made a substantial significant contribution to firm output [ 28 ], force financial services institutions to adopt technologies that help deliver high-quality services at a minimal cost [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the studies of the digital economy on the environmental field and green development, such as promoting the clean energy development [8], Optimizing Urban Carbon Emissions [9], Control of urban environmental pollution, etc. [10]. The third aspect is the impact on other industries, such as tourism [11][12][13], development of manufacturing industry [14], the business model of creative industry, etc.…”
Section: Introductionmentioning
confidence: 99%